Welcome to Westonci.ca, where your questions are met with accurate answers from a community of experts and enthusiasts. Explore our Q&A platform to find in-depth answers from a wide range of experts in different fields. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
first step to solve (v+6)(v-6)=0 is to use FOIL and dd the multiplication
v^2-6v+6v-36=0
v^2-36=0\ or v^2=36
we need to take the square root from both sides so
v=6 and v=-6
v = {-6, 6}
v^2-6v+6v-36=0
v^2-36=0\ or v^2=36
we need to take the square root from both sides so
v=6 and v=-6
v = {-6, 6}
We appreciate your visit. Hopefully, the answers you found were beneficial. Don't hesitate to come back for more information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. Keep exploring Westonci.ca for more insightful answers to your questions. We're here to help.